2015
DOI: 10.1515/cclm-2013-1088
|View full text |Cite
|
Sign up to set email alerts
|

Long-term biological variability of galectin-3 after heart transplantation

Abstract: The concentrations of galectin-3 in patients followed 12 months after HTx fluctuated around the homeostatic point, with CVi of approximately 28%. RCVs of +116% (log-normal increase) and -54% (log-normal decrease) mean that the concentration of galectin-3 would need to approximately double or decrease by half to indicate a new process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Galectin-3 analyzed 10 days following HT displayed an association with heart function assessed 1 year after HT ( 92 ). Furthermore, galectin-3 fluctuated in patients followed up for 12 months after HT, and a novel process was indicated when galectin-3 increased by double or decreased by one-half compared to the baseline level ( 93 ). Contrastingly, Grupper et al ( 94 ) reported that although the galectin-3 expression level increased despite HT, and was associated with renal dysfunction, it was not associated with the presence of myocyte hypertrophy and interstitial fibrosis post HT ( 94 ).…”
Section: Galectin-3 and Cardiovascular Diseasementioning
confidence: 99%
“…Galectin-3 analyzed 10 days following HT displayed an association with heart function assessed 1 year after HT ( 92 ). Furthermore, galectin-3 fluctuated in patients followed up for 12 months after HT, and a novel process was indicated when galectin-3 increased by double or decreased by one-half compared to the baseline level ( 93 ). Contrastingly, Grupper et al ( 94 ) reported that although the galectin-3 expression level increased despite HT, and was associated with renal dysfunction, it was not associated with the presence of myocyte hypertrophy and interstitial fibrosis post HT ( 94 ).…”
Section: Galectin-3 and Cardiovascular Diseasementioning
confidence: 99%